'It Looks Like You Just Want Them When Things Get Rough': Civil Society Perspectives on Negative Trial Results and Stakeholder Engagement in HIV Prevention Trials. Issue 3 (24th September 2012) - Koen, Jennifer; Essack, Zaynab; Slack, Catherine; Lindegger, Graham; Newman, Peter A.
Abstract Civil society organizations (CSOs) have significantly impacted on the politics of health research and the field of bioethics. In the global HIV epidemic, CSOs have served a pivotal stakeholder role. The dire need for development of new prevention technologies has raised critical challenges for the ethical engagement of community stakeholders in HIV research. This study explored the perspectives of CSO representatives involved in HIV prevention trials (HPTs) on the impact of premature trial closures on stakeholder engagement. Fourteen respondents from South African and international CSOs representing activist and advocacy groups, community mobilisation initiatives, and human and legal rights groups were purposively sampled based on involvement in HPTs. Interviews were conducted from February‐May 2010. Descriptive analysis was undertaken across interviews and key themes were developed inductively. CSO representatives largely described positive outcomes of recent microbicide and HIV vaccine trial terminations, particularly in South Africa, which they attributed to improvements in stakeholder engagement. Ongoing challenges to community engagement included the need for principled justifications for selective stakeholder engagement at strategic time‐points, as well as the need for legitimate alternatives to CABs as mechanisms for engagement. Key issues for CSOs in relation to research were also raised.